Nepal's Experiment With Democracy - "Chatterjee, Bhola" (New Delhi, 1977)
This book is about Nepal's experiment with democracy and covers the following topics Mutual Indictments; Change and continuity; A state of Flux and Election Brings Stability etc.
Keywords: Democracy